Particle Processing of Acetaminophen using Cooling and Anti-solvent Crystallization Methods - Kurniawansyah, Firman; Ahmad, Fathanudin; Widagda, Indra Cahya; Idzati, Eka Maulana; Ni'mah, Hikmatun; Mahfud, Mahfud (The Journal of Pure and Applied Chemistry Research, 2024)
Several crystallization strategies are being implemented to enhance the solubility of acetaminophen, also known as paracetamol. Therefore, this study aimed to determine the effectiveness of the cooling and anti-solvent crystallization on the properties of acetaminophen. The results showed that the anti-solvent recrystallization produced achieved an impressive yield of up to 41.40%, while the cooling method yielded approximately 2â€“9%. Through FTIR, XRD, and DSC analysis on the samples, it was discovered that these methods had minimum effects on the molecular and thermal properties of the compound. Furthermore, the methods did not alter the crystallinity of acetaminophen, with crystal form I dominating the products. In addition, processing using the cooling and anti-solvent effectively reduced particle size of acetaminophen from 68.60 Î¼m to 26.92 Î¼m and 28.25 Âµm, respectively. In conclusion, the solubility of paracetamol in aqueous solutions experienced a significant enhancement. In the unprocessed samples, it measured 0.0107 gram/ml, while the recrystallized samples had an improved range of 0.0123 to 0.0167 g/ml.